2023
DOI: 10.3390/metabo13010114
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Quorum Sensing Molecules in Bacterial–Plant Interactions

Abstract: Quorum sensing (QS) is a system of communication of bacterial cells by means of chemical signals called autoinducers, which modulate the behavior of entire populations of Gram-negative and Gram-positive bacteria. Three classes of signaling molecules have been recognized, Al-1, Al-2, Al-3, whose functions are slightly different. However, the phenomenon of quorum sensing is not only concerned with the interactions between bacteria, but the whole spectrum of interspecies interactions. A growing number of research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 151 publications
0
12
0
Order By: Relevance
“…Biofilm formation and maturation are mainly regulated by quorum sensing (QS), which depends on the synthesis of small signal molecules that regulate virulence factor expression and biofilm development in a density-dependent manner [ 5 ]. Acyl-homoserine lactones (AHLs) are important QS-related signaling molecules that are mainly produced by Gram-negative bacteria [ 6 ]. AHLs have been isolated from several oral pathogens in dentine caries and dental plaque [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biofilm formation and maturation are mainly regulated by quorum sensing (QS), which depends on the synthesis of small signal molecules that regulate virulence factor expression and biofilm development in a density-dependent manner [ 5 ]. Acyl-homoserine lactones (AHLs) are important QS-related signaling molecules that are mainly produced by Gram-negative bacteria [ 6 ]. AHLs have been isolated from several oral pathogens in dentine caries and dental plaque [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The actions of mycorrhizae and PGPR can mitigate these effects by intervening in the ROS compounds produced in the root system, thereby reducing the mimetic and catalytic peroxidase-like activity of CeNPs. [90][91][92][93][94][95][96] Considering climate change, these conditions characterized by reduced water and humidity content in soils are expected to become increasingly prevalent. In such scenarios, in addition to the abovementioned effects, different studies reported a direct beneficial effect of nCeO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The disease cycle, which comprises differentiated stages and is represented in Figure 1, starts with a source of inoculum and ends with the appearance of symptoms such as tumors [106], decay and chlorosis [107], blight [108], wilting [109], rot [110], and cankers [111]. QS is responsible for regulating pathogenicity and colonization [83,112], and some phytopathogenic bacteria may have more than one QS system (featuring AHLs or diffusible signal factors, DSF) as well as a virulence factor modulation system [113]. For bacteria such as E. amylovora, P. syringae, Xanthomonas spp., and Ralstonia spp., T3SS are also involved in pathogenesis since they enable the direct introduction of pathogenic proteins into host cells.…”
Section: Biofilm Formed By Phytopathogenic Bacteriamentioning
confidence: 99%
“…The synthesis of these polymers and that of cellulose, another component of the biofilm matrix, are positively regulated by an increase in intracellular c-di-GMP [82,115]. QS is responsible for regulating pathogenicity and colonization [83,112], and some phytopathogenic bacteria may have more than one QS system (featuring AHLs or diffusible signal factors, DSF) as well as a virulence factor modulation system [113]. For bacteria such as E. amylovora, P. syringae, Xanthomonas spp., and Ralstonia spp., T3SS are also involved in pathogenesis since they enable the direct introduction of pathogenic proteins into host cells.…”
Section: Phytopathogenic Bacteria That Colonize Xylem Vesselsmentioning
confidence: 99%